PLANNING (PERENCANAAN) DALAM MANAJEMEN PENDIDIKAN ISLAM - Imaniyah (Journal of Innovation Research and Knowledge, 2022)
Planning is needed by various forms of organization, because this planning is the basic process of management in making decisions and actions. Planning is needed in any type of activity, whether it be organizational, corporate or community activities, and planning exists in every management function, because these functions can only carry out the decisions that have been determined in the planning. This article aims to explain the importance of planning in the Islamic education system. The results show that in management, planning is the process of defining organizational goals, creating strategies to achieve those goals, and developing organizational work activity plans. Planning is the most important process of all management functions because without planning the other functions of organizing, directing, and controlling will not be able to run. Good planning will result in good management. It is better to take decisions and actions in various forms of organization using the basic management process in the form of planning. In a plan, it is necessary to pay attention to the nature of a good plan to achieve the desired results.